Trop2 Promotes Vimentin Expression and Induces Epithelial Stromal Transformation, Invasion and Metastasis of Gastric Cancer Cells by Regulating β-Catenin: Trop2 Promotes Vimentin Expression - Guo, Wei; Jia, Li; Wang, Donghui; Wang, Zhenhua; Li, Ruichao; Xue, Zhaojun (Cellular and Molecular Biology, 2023)
One of the most critical biological characteristics of gastric cancer (GC) is invasion and metastasis, which is also the main factor of recurrence and drug resistance. Epithelial intermediate transformation is a biological process. Epithelial cells lose the ability to exercise their epithelial characteristics while acquiring parental characteristics. Malignant epithelial cancer cells lose their connectivity and polarity through the EMT process, change cell morphology and enhance their migration ability, so as to gain the ability of invasion and variation. In this paper, we proposed that trop2 can promote vimentin expression by regulating β - Catenin to induce the transformation and metastasis of gastric cancer cells. In this study, a control group experiment was set up to construct mkn45tr and nci-n87tr resistant cell lines. The results showed that the resistance index (RI) of mkn45tr was 31.33, P < 0.01; the resistance index (RI) of nci-n87tr was 108.23, P < 0.01. The results show that the drug resistance of gastric cancer cells will become stronger with the change of time.